1990
DOI: 10.1042/cs0780221
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of broadband ultrasound attenuation in the os calcis in vitro

Abstract: 1. We have examined the relationship between the attenuation of broadband ultrasound in the os calcis in vitro and its bone mineral density measured by quantitative computed tomography and by physical density. 2. Broadband ultrasound attenuation was found to correlate closely with physical density (r = 0.85, P less than 0.0001), but the correlation was less than that observed between quantitative computed tomography and physical density (r = 0.92, P less than 0.0001). Measurements of broadband ultrasound atten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
20
0
2

Year Published

1991
1991
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(26 citation statements)
references
References 10 publications
3
20
0
2
Order By: Relevance
“…However, since there are good correlations between velocity measured with and without soft tissue, it may not be necessary to adjust velocity for the effect of soft tissue. Similarly, in agreement with McCloskey et al [7] there seems to be no need to adjust BUA for the effect of soft tissue since there was no difference between BUA measured through bone plus soft tissue and bone alone (water method). In contrast, the apparent mismatch between the value of 4 cm defined by Lunar Achilles as heel width and the actual measured heel widths creates a significant difference in calculated velocities.…”
Section: Influence Of Soft Tissue and A Fixed Heel Dimensionsupporting
confidence: 87%
See 1 more Smart Citation
“…However, since there are good correlations between velocity measured with and without soft tissue, it may not be necessary to adjust velocity for the effect of soft tissue. Similarly, in agreement with McCloskey et al [7] there seems to be no need to adjust BUA for the effect of soft tissue since there was no difference between BUA measured through bone plus soft tissue and bone alone (water method). In contrast, the apparent mismatch between the value of 4 cm defined by Lunar Achilles as heel width and the actual measured heel widths creates a significant difference in calculated velocities.…”
Section: Influence Of Soft Tissue and A Fixed Heel Dimensionsupporting
confidence: 87%
“…In either case the effects of soft tissue (skin, subcutaneous tissue, marrow) and pathlength (distance traveled by the US beam through the various tissues) are usually ignored. The presence of soft tissue causes a significant reduction in SOS whereas broadband ultrasonic attenuation (BUA) appears to be relatively insensitive to soft tissue effects [6][7][8]. Though there would appear to be little support for an effect of bone width on BUA [8,9], a recent report [10] using cancellous bovine bone (femora) found a strong positive correlation between these variables (r ‫ס‬ 0.92).…”
mentioning
confidence: 96%
“…B U A of the calcaneus correlates with bone density measurements at the same site [8], and with total bone volume determined by histomorphometric techniques at the same site [4]. This preliminary study demonstrates that B U A of the calcaneus can be used to predict BMD of the spine and femur with a low SEE.…”
Section: Discussionmentioning
confidence: 78%
“…The limitation of the technology is that the relationship between the us parameters measured and trabecular structure is not fully understood but there have been some associations reported. Ultrasound transmission velocity, VOS, is proportional to the elastic modulus, compressive, and yield strengths of the bone [22] and there is a good correlation between BUA and physical density (r ‫ס‬ 0.85, P < 0.0001 [23]). In vitro studies of trabecular microstructure have demonstrated an inverse correlation between the us transmission velocity and the degree of trabecular separation [24].…”
Section: Discussionmentioning
confidence: 99%